Correlation between Sleep Quality That Influences the Mental Health of Global Islamic School (GIS) Students in The Covid-19 Pandemic - Wahjuningtijas, Rindang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Sleep is one of the factors of optimal health and vitality. Sleep quality       is the measurement on how well you are sleeping, whether your sleep is restful, restorative, and healthful. Addressing sleep problems early-on is important to help protect your overall health. An underlying sleep disorder or a medical condition might be playing a role in your sleep issues. With the COVID-19 pandemic implementation of lockdown, people’s sleep quality has begun to be disturbed and mental disorders have increased in Indonesia. To find out if sleep quality, mental health, and pandemic in Senior High School GIS Students are related to each other. The type of the study in this paper is quantitative research. To convene the data, the author handed out an online questionnaire to 50 students of Senior High GIS. Pearson’s correlation statistical test had a significant result that there was a relationship between the effect of COVID-19 Pandemic on sleep quality and mental health. Sleep quality can be affected to the mental health by the effect of COVID-19 Pandemic.